EFISIENSI ENERGI PRODUKSI ECOPRINT UNTUK MENINGKATKAN PRODUKTIFITAS HASIL USAHA - Imam Saukani; Sulistyono, Sulistyono; Zakijah Irfin; Diana Eka Poernamawati (Bajang Institute, 2025)
Ecoprint is a fabric dyeing technique that utilizes natural materials such as leaves, flowers, and twigs to create unique patterns on fabric, promoting environmental sustainability. While this technique offers ecological benefits, the manual heating process used to fix the colors is often inconsistent and time-consuming. This research aims to develop a controlled heating system based on a minimum system to improve the efficiency and quality of ecoprint production. The system allows for precise temperature control at 90°C and automatic heating duration, ensuring stable temperatures and optimized time settings. The trial results indicate that the controlled heating system produces more consistent patterns, sharper colors, and reduces the risk of fabric damage compared to manual heating methods. Additionally, the system is capable of saving up to 20% in energy consumption and lowering operational costs. The implementation of this technology has a positive impact on the productivity of small and medium enterprises (SMEs), enhances product quality, and expands the market potential for ecoprint products. Therefore, this controlled heating technology not only improves production efficiency but also supports the sustainability of creative industries based on local wisdom and environmentally friendly practices